2015
DOI: 10.1080/14616734.2015.1120334
|View full text |Cite
|
Sign up to set email alerts
|

Attachment in middle childhood: predictors, correlates, and implications for adaptation

Abstract: Middle childhood is a relative lacuna in behavioral attachment research. We examined antecedents, correlates, and implications of parent-child attachment at age 10 in a longitudinal study of community families from a Midwestern US state (N=102, mothers, fathers, and children). Dimensions of security, avoidance, ambivalence, and disorganization of children’s attachment to each parent were observed in lengthy naturalistic interactions and assessed using Iowa Attachment Behavioral Coding (IABC). IABC scores were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 70 publications
5
33
0
3
Order By: Relevance
“…Within the context of disorganization of attachment, reversal reflects fuzzy boundaries and roles, intrusiveness, over-protectiveness, and enmeshment (Jacobvitz, Morgan, Kretchmar & Morgan, 1991). However, role reversal could also be seen as an organized strategy, reflecting the child's efforts to use an adaptive strategy to accomplish his/her attachment needs and closeness to the caregiver (Boldt, Kochanska, Grekin & Brock, 2016). Notably, previous research has demonstrated that while role reversal in the form of caregiving behavior in the child is associated with more helpless and passive parenting (Lyons-Ruth, Yellin, Melnick & Atwood, 2005;Moss, Bureau, Beliveau, Zdebik & Lepine, 2009), punitive behavior is more common when the child experiences parental hostility and intrusiveness (Solomon & George, 2008).…”
Section: Intrusive and Conflictual Behaviors In Children's Representamentioning
confidence: 99%
“…Within the context of disorganization of attachment, reversal reflects fuzzy boundaries and roles, intrusiveness, over-protectiveness, and enmeshment (Jacobvitz, Morgan, Kretchmar & Morgan, 1991). However, role reversal could also be seen as an organized strategy, reflecting the child's efforts to use an adaptive strategy to accomplish his/her attachment needs and closeness to the caregiver (Boldt, Kochanska, Grekin & Brock, 2016). Notably, previous research has demonstrated that while role reversal in the form of caregiving behavior in the child is associated with more helpless and passive parenting (Lyons-Ruth, Yellin, Melnick & Atwood, 2005;Moss, Bureau, Beliveau, Zdebik & Lepine, 2009), punitive behavior is more common when the child experiences parental hostility and intrusiveness (Solomon & George, 2008).…”
Section: Intrusive and Conflictual Behaviors In Children's Representamentioning
confidence: 99%
“…The issue of measurement of attachment in middle childhood remains more unsettled, as the upsurge of attention towards attachment in middle childhood from researchers and clinicians during the last decade has led to the development of several different measures, with varying focus and underlying assumptions, and few studies have scrutinized whether and how these different measures converge (e.g., Di Folco, Messina, Zavattini & Psouni, ; Psouni & Apetroaia, ). While attachment questionnaires elicit descriptions of behaviors with parents (e.g., the Security Scale: Kerns, Aspelmeier, Gentzler & Grabill, ), behavioral measures follow the paradigm used for attachment assessment in infancy and early childhood and observe the child’s behavior towards a specific caregiver, in situations likely to activate the attachment system (see Boldt, Kochanska, Grekin & Brock, ; Brumariu et al ., ; Bureau, Easterbrooks & Lyons‐Ruth, ). Adopting a representational focus, narrative‐based measures use carefully selected word‐probes and attachment‐related story themes to access children’s (implicit) attachment scripts as components of their attachment representations (e.g., the Secure Base Script Test: Psouni & Apetroaia, ).…”
Section: Introductionmentioning
confidence: 99%
“…The scarce observational studies on attachment in middle childhood (and adolescence) use macro-coding approaches in which certain aspects of the behavior of mother and/or child during an interaction are rated. The rating scales measure attachment-relevant dimensions, such as the amount of parental sensitivity and child responsiveness (Emotional Availability Scale) [9], security, avoidance, ambivalence and disorganization of the child (Iowa Attachment Behavior Coding) [10], parent’s or adolescent’s punitive or role-confusing behavior (Goal‐Corrected Partnership in Adolescence Coding System) [11,12], secure, ambivalent and disorganized attachment behavior of the child (Middle Childhood Attachment Strategies) [5]. Clearly, such macro-coding approaches provide detailed and rich scores.…”
Section: Introductionmentioning
confidence: 99%